Representation of Environmental Based Arts Education: A Case Study of Cultural Heritage Through The Balahak Performance in Siulak Mukai Kerinci Jambi - Dilfa, Alrizka Hairi; Hartono, Hartono; Sumaryanto Florentinus, Totok (Catharsis, 2020)
The aim of this study is to analyze the representation of environmental based arts education through cultural heritage through Balahak performance in Siulak Mukai, Kerinci - Jambi. The research method of this study uses qualitative data types and case study research design, for the data sources in this study uses primary and secondary data sources, for the data collection techniques in this study uses observation techniques, interviews, and document study. The data analysis technique in this study was analyzed by using interactive data analysis. The results of this study provide two evidences. First, Balahak is a performing art that is generally known as a bridal procession in Siulak Mukai. Balahak includes three processes, namely Bakumpu, Balahak, and Ba'uwu. Second, Balahak can be a means of cultural heritage to enculturate for participants (presenters) and socialize for the audience. It shows a reciprocal relationship between humans and the natural environment, the social environment and the environment in the balahak performance process, thus it makes balahak as a means to regenerate and introduce culture which is concluded as cultural heritage that represents environmental based arts education.